Multi-team robot system (MTRS) with zigbee communication technology - Lim, Cheng Siong (2007)
Zigbee communication is specially built for control and sensor networks on IEEE 802.15.4 standard for wireless personal area networks (WPANs), and it is the product from Zigbee alliance. This communication standard defines physical and Media Access Control (MAC) layers to handle many devices at low-data rates.